2018
DOI: 10.1021/acsnano.8b05891
|View full text |Cite
|
Sign up to set email alerts
|

Field-Effect Device Using Quasi-Two-Dimensional Electron Gas in Mass-Producible Atomic-Layer-Deposited Al2O3/TiO2 Ultrathin (<10 nm) Film Heterostructures

Abstract: We report the field-effect transistors using quasi-two-dimensional electron gas generated at an ultrathin (∼10 nm) AlO/TiO heterostructure interface grown via atomic layer deposition (ALD) on a SiO/Si substrate without using a single crystal substrate. The 2DEG at the AlO/TiO interface originates from oxygen vacancies generated at the surface of the TiO bottom layer during ALD of the AlO overlayer. High-density electrons (∼10 cm) are confined within a ∼2.2 nm distance from the AlO/TiO interface, resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 29 publications
4
43
0
Order By: Relevance
“…Application of a V GS < 0 V can shut down the channel by an identical mechanism. A similar phenomenon has been reported for other 2DEG TFTs …”
Section: Performance Metrics Of the Indicated Tft Devices On Si/sio2 supporting
confidence: 89%
“…Application of a V GS < 0 V can shut down the channel by an identical mechanism. A similar phenomenon has been reported for other 2DEG TFTs …”
Section: Performance Metrics Of the Indicated Tft Devices On Si/sio2 supporting
confidence: 89%
“…An amorphous Al 2 O 3 film, with a thickness of ≈3 nm, was grown on the crystalline TiO 2 (≈10 nm) layer. This TiO 2 layer was a polycrystalline anatase phase, as reported by our group . The interface between the Al 2 O 3 and TiO 2 layers was sharp, which implies that the layers did not intermix.…”
Section: Resultssupporting
confidence: 73%
“…Unfortunately, the electron density could not be tailored for the given fabrication method, in which electrons originated from the polar catastrophe mechanism based on the epitaxial interface . For the Al 2 O 3 /TiO 2 heterostructure, it has been reported that oxygen vacancies were generated on the surface of the TiO 2 layer during the Al 2 O 3 ALD process . By the action of trimethylaluminum (TMA), which is an Al‐precursor in the Al 2 O 3 ALD process, Ti 4+ in the fully oxidized TiO 2 layer reduces to Ti 3+ on the surface of the TiO 2 layer, which causes the generation of oxygen vacancies on the TiO 2 surface, as reported in ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations